2008
DOI: 10.1016/j.joca.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adenosine receptors in bovine chondrocytes and fibroblast-like synoviocytes exposed to low frequency low energy pulsed electromagnetic fields

Abstract: PEMFs mediate an up-regulation of A2A and A3 receptors related to an increase of their functional activities in bovine chondrocytes and fibroblast-like synoviocytes. No differences are present in adenosine affinity and in the drug-receptor interactions. Our data could be used as a trigger to future studies addressed to PEMFs and adenosine therapeutic intervention in inflammatory joint diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 45 publications
5
123
0
1
Order By: Relevance
“…Chondrocytes are known to express all the P1 receptors (Tesch et al, 2002;Varani et al, 2008a); however, information regarding the functional effects of receptor activation remains limited. Pulsed electro-magnetic fields have been shown to promote chondrocyte proliferation via the up-regulation of A2A and A3 receptor expression (Varani et al, 2008a).…”
Section: P1 Receptors and Chondrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chondrocytes are known to express all the P1 receptors (Tesch et al, 2002;Varani et al, 2008a); however, information regarding the functional effects of receptor activation remains limited. Pulsed electro-magnetic fields have been shown to promote chondrocyte proliferation via the up-regulation of A2A and A3 receptor expression (Varani et al, 2008a).…”
Section: P1 Receptors and Chondrocytesmentioning
confidence: 99%
“…Pulsed electro-magnetic fields have been shown to promote chondrocyte proliferation via the up-regulation of A2A and A3 receptor expression (Varani et al, 2008a). Adenosine, acting via A2A receptors, can also reduce IL-1β-induced inflammation (Campo et al, 2012) and VEGF secretion (Vincenzi et al, 2013).…”
Section: P1 Receptors and Chondrocytesmentioning
confidence: 99%
“…Several investigations have been carried out to assess the efficacy of PEMFs in patients with OA but the results have been contradictory [20,22]. Thamsborg et al 18 conducted a Randomized Clinical Trial (RCT) including 83 patients and found no significant differences in the outcome scores in the group treated with PEMFs compared to a placebo group [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a RCT evaluating the outcomes of arthroscopic chondro-abrasion or perforation followed by treatment with PEMF, Zorzi et al showed that PEMFs aided patient recovery by reducing the requirement of analgesics. The use of PEMFs was associated with improved functional outcomes associated with a long-term effects [22]. However, the cartilage procedure creates a confounding factor and questions the actual benefit of PEMF in the long run.…”
Section: Discussionmentioning
confidence: 99%
“…Later, it was demonstrated that chondrocytes respond to adenosine via A 2 receptors, activity which was potentiated by adenosine deaminase (ADA) and phosphodiesterase inhibitors [337]. Furthermore, pulsed electromagnetic fields produce an up-regulation of the A 2A and A 3 receptors that mediate proliferation of bovine chondrocytes and fibroblast-like synoviocytes [338], and A 2A receptor activation reduces inflammation in mouse articular chondrocytes stimulated with IL-1β [339].…”
Section: P1 Receptors Adenosine and Chondrocytesmentioning
confidence: 99%